Subacromial Anesthetics Increase Proprioceptive Deficit in the Shoulder and Elbow in Patients With Subacromial Impingement Syndrome. Issue 10 (8th June 2017) - Ettinger, Lucas R; Shapiro, Matthew; Karduna, Andrew
Shoulder proprioception gives information regarding arm joint position and movement direction. Several studies have investigated shoulder proprioceptive acuity in patients with subacromial impingement syndrome (SIS); however, differences in protocols and between-subjects designs have limited scientific inferences regarding proprioception and SIS. We aimed to determine within-subject differences in shoulder and elbow proprioceptive acuity in 17 patients with stage 2 SIS following treatment of a local anesthetic injection. In addition, we used 17 healthy, age-, sex-, and arm dominance–matched controls to determine the magnitude of differences after treatment. Joint position sense (JPS) was measured before and after treatment in both groups in the sagittal plane for the shoulder and elbow. Our results indicate that patients with SIS have less sensitivity to angular position and tended to overshoot their targets with greater variability during angle-matching tasks for the shoulder (1.8° difference, P  = .042) and elbow (5.6° difference, P  = .001) than controls. The disparities in JPS found in patients with SIS were not resolved following subacromial injection; in fact, the magnitude of the errors increased after treatment where postinjection errors were significantly greater ( P  = .046) than controls, with an average difference of 2.4°. These findings suggest that patients with SIS have decrements in either the signaling or processing of proprioceptive information and may use pain to reduce these inequalities.